The Influence of Digital Literacy of Educators Based on Artificial Intelligence (AI) on Learning Effectiveness and Educator Performance - Wulandari, Hodijah; Sutarto, Joko; Ahmadi, Farid (Jurnal Locus Penelitian dan Pengabdian, 2024)
This study examines the effect of digital literacy of educators based on Artificial Intelligence (AI) on learning effectiveness and educator performance in the Non-Formal Education Unit of the Learning Activity Center (SKB) in Pekalongan Prefecture. This research is quantitative causal research. With a population of 132 educators and a sample of 101 educators using a simple random sampling, data were collected through questionnaires and analyzed descriptively and simple linear regression. The findings indicated that the digital literacy of AI-based educators positively and significantly influenced learning effectiveness (59.1%) and educator performances (54%), with a significance value of 0.000 <0.005. The research conclusion emphasizes the importance of improving digital literacy through training and collaboration and the need for support from agencies and the government in providing access to technology and adequate infrastructure. Future investigations will examine additional independent variables that could impact educational outcomes.